Half the sky : turning oppression into opportunity for women worldwide - Kristof, Nicholas D., 1959-; WuDunn, Sheryl, 1959- (New York : Alfred A. Knopf, 2009)
Two Pulitzer Prize winners issue a call to arms against our era's most pervasive human rights violation: the oppression of women in the developing world. They show that a little help can transform the lives of women and girls abroad and that the key to economic progress lies in unleashing women's potential.
The girl effect -- Emancipating twenty-first-century slaves -- Fighting slavery from Seattle -- Prohibition and prostitution -- Rescuing girls is the easy part -- Learning to speak up -- The new abolitionists -- Rule by rape -- Mukhtar's school -- The shame of "honor" -- "Study abroad"-- in the Congo -- Maternal mortality, one woman a minute -- A doctor who treats countries, not patients -- Why do women die in childbirth? -- Edna's hospital -- Family planning and the "God gulf" -- Jane Roberts and her 34 million friends -- Is Islam misogynistic? -- The Afghan insurgent -- Investing in education -- Ann and Angeline -- Microcredit : the financial revolution -- A CARE package for Goretti -- The axis of equality -- Tears over Time magazine -- Grassroots vs treetops -- Girls helping girls -- What you can do -- Four steps you can take in the next ten minutes -- Appendix. Organizations supporting women.
Includes bibliographical references (p. 259-278) and index.
Keywords: Women's rights -- Developing countries -- Case studies; Women -- Crimes against -- Developing countries -- Case studies; Women -- Developing countries -- Social conditions -- Case studies